Pro12Ala Polymorphism on the PPARγ2 Gene and Weight Loss After Aerobic Training: A Randomized Controlled Trial - Cardoso, Glêbia Alexa; Persuhn, Darlene Camati; Ribeiro, Mateus Duarte; de Sousa, Bruno Rafael Virgínio; Sena, Klécia de Farias; de Almeida, Antônio Eduardo Monteiro; Modesto-Filho, João; da Silva, Raquel Suelen Brito; Silva, Alexandre Sérgio (Frontiers in Physiology, 2020)
The objective of the study was to verify the influence of the Pro12Ala polymorphism on the PPARγ2 gene response of a program training on body composition. Sixty nine previously inactive men and women (32.8 ± 8.2 years) were genotyped and underwent a 12-week aerobic (running / walking) program (3 to 5 sessions, 40 - 60 minutes per session, intensity between aerobic and anaerobic threshold) (experimental group n=53) or control group (n=16). They were tested for aerobic capacity, body composition (DXA), abdomen, waist and hip circumferences and nutritional assessment before and 48 hours after the experimental protocol. Two-way repeated measures ANOVA test was used to verify possible differences in variables between the experimental vs. control groups or Pro / Pro vs. Pro / Ala groups, and Chi-squared test was used to verify the distribution of responders and non-responders according to genotype (p < 0.05). A frequency of 75.5% pro / Pro and 24.5% pro / ala were found, without any occurrence of the recessive homozygote. Body fat reduction was initially confirmed compared to a control group that did not exercise (n = 16; 29.1 ± 8.8 years), so that the exercised group obtained reduction of -1.3kg versus -0.3kg in the control group (p = 0.03). When divided by genotype, there were significant changes in fat mass (-1.3 ± 2.1 kg;p = 0.00), lean mass (0.6 ± 1.5kg; p = 0.02), fat Percentage (-1.3 ± 1.6; p = 0.00), waist circumference (-2.2 ± 2.9cm; p = 0.00), abdomen circumference (-3.3 ± 3.6cm; p = 0.00) and hip circumference (-2.7 ± 2.7cm; p = 0.00) for genotyps Pro / Pro; and fat mass (-1.1 ± 1.7kg; p = 0.04), fat Percentage (-0.9 ± 1.5; p = 0.04), abdomen circumference (-3.9 ± 3.5cm; p = 0.00) and hip circumference (-1.8 ± 1.8cm; p = 0.00) for genotyps Pro / Ala, without group interaction differences. Qui square revealed no different distribution of responders or non-responders according to genotype. Concluded that an aerobic training program promotes weight loss, but the Pro12Ala polymorphism in the PPARγ2 gene does not influence the variability of aerobic-induced exercise weight loss.